An Effective Method to Estimate the Aggregated Flexibility at Distribution Level - Nikolaos Savvopoulos; Nikos Hatziargyriou (IEEE Access, 2023)
The exploitation of flexibility services provided by distributed energy resources (DERs) located in the distribution grid becomes increasingly important for the secure and reliable operation of power systems. These resources are typically small-scale and located close to end-users, however their aggregated flexibility can offset the imbalance caused by the stochastic variations of the Renewable Energy Sources (RES). This paper proposes a methodology to estimate with increased accuracy the available flexibility of DERs in an Active Distribution Grid (ADG) at the point of interconnection with the transmission system. An optimization-based approach is used to estimate the available maximum active and reactive power flexibility for specific search directions formed by constant active to reactive power ratios. In order to keep calculations manageable and estimate the available flexibility with high accuracy, the search directions are sampled from a distribution that is iteratively updated at each step. Three variations are proposed for the angle sampling, both in the angle domain and in the p-q domain. Each variation is tested on a modified 18-bus radial distribution system and its effectiveness and convergence is compared.